The Teziutlan Copper-Zinc Deposit, Teziutlan, Puebla, Mexico (b625b24b-f03a-45d5-9b5a-dbd3de3cf999) - A. W. Edelen; H. V. Lee (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1937)
THE Teziutlan copper-zinc deposit is supposed to be of late Cambrian or early Paleozoic age. The country rocks are a series of schists or phyllites, flat lying and in the form of a plunging anticline. The ore deposit occupies a single horizon in the schist for a known horizontal extent of 1200 meters. Along its strike occur four large lenses or ore bodies. These ore bodies occupy positions along the flank and extend to the crest of the anticline. The primary mineralization is in the form of quartz, pyrite, sphalerite, chalcopyrite and galena, with a few scattered silver anti-monides. Quartz and pyrite form the mineralization between the ore lenses. In the ore lenses the sulphides appear as a massive, very he-grained intergrowth of minerals. The intergrowth suggests a contemporaneous deposition of the heavy sulphides. The grain size, usually under 0.09 mm., makes the separation difficult and fine grinding important. The ore bodies were formed at great depth by solutions probably originating in the same basic magma that gave rise to the dolerite sills that are so common in their vicinity. INTRODUCTION The Teziutlan copper-zinc deposit is distinctly different from other ore deposits of Mexico in age and type. Previously stated to be pre- Cambrian in age, it is now quite generally supposed to belong to the late Cambrian or to the early Paleozoic period. Also, in contrast to the usual shallow-vein zone type of mineralization in Mexico, there is here exemplified an intermediate vein zone deposit of copper and zinc. So far as is known, the Teziutlan vein is unique in the history of Mexican geology and in a class by itself, its closest counterpart probably being the copper veins of the pre-Cambrian of Canada. The Teziutlan district is in the extreme northwestern corner of the State of Puebla, Mexico. Teziutlan, the terminus of a branch line of the National Railways from Mexico City, is connected to the mine at Aire Libre by a 17-km. narrow-gauge railroad owned and operated by the Teziutlan Copper Co. Owing to excessive grades on this short line, Shay-geared locomotives are used for the transportation of concentrates and supplies.